Kemampuan Pengawas Madrasah/PAI Menyusun dan Mengimplementasikan Rencana Tindak Lanjut Praktik Pengawasan pada Peserta Diklat Penguatan Kompetensi Pengawas Madrasah/PAI di Daerah Istimewa Yogyakarta - Siti Aminah (Balai Diklat Keagamaan Semarang, 2020)
The purpose of this study is to determine the ability of Madrasah/PAI supervisors in compiling and implementing a Supervisory Practice Follow-Up Plan (RTLPP) for participants in the Training for Strengthening Competence of Madrasah/ PAI Supervisors organized by the Semarang Religious Education and Training Center in 2019. The research method used is descriptive quantitative. The subjects in this study were 40 Madrasah/PAI supervisors who participated in the Training of Strengthening the Competence of Madrasah/PAI Supervisors in the Special Region of Yogyakarta. The results showed that 33 respondents (82.5%) were able to compile the RTLPP in the very good category, and 7 respondents (17.5%) reached the good category. As for the ability to implement RTLPP, 22 respondents (55%) achieved the very good category, and 18 respondents (45%) achieved the good category.